2020
DOI: 10.1002/bse.2630
|View full text |Cite
|
Sign up to set email alerts
|

Managing sustainability in luxury industry to pursue circular economy strategies

Abstract: Sustainable luxury research has received growing attention in the most recent years as it requires firms and supply chains to design circular business models and strategies to tackle environmental, financial, and social issues. However, previous research still falls short to deepen how luxury firms design and manage sustainable supply chain practices according to the circular principles. This paper adopts bibliometric and network analysis to evaluate a sample of 747 papers published over the last 35 years. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 161 publications
0
27
0
Order By: Relevance
“…The authors demonstrated that the processing and conservation of resources allows the company to save production costs and maximize profits. This is why the questions raised regarding the formation of the mechanism of the strategic potential of the enter-prise in the conditions of a circular economy will reduce the influence on the ecological environment [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors demonstrated that the processing and conservation of resources allows the company to save production costs and maximize profits. This is why the questions raised regarding the formation of the mechanism of the strategic potential of the enter-prise in the conditions of a circular economy will reduce the influence on the ecological environment [28].…”
Section: Discussionmentioning
confidence: 99%
“…Research on the formation of a circular economy has been conducted by many scientists [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. From the point of view of the implementation of the circular economy, the innovative potential of enterprises is also significant [30][31][32].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The procedure used in the paper to answer the research questions presented in the introduction covers several stages (Bartolacci et al, 2020;Ferasso et al, 2020). The procedure was also discussed by Shashi et al (2021) and Suchek et al (2021). The flowchart of the procedure developed for the literature review has been presented in Figure 2.…”
Section: The Adopted Procedures Of the Systematic Literature Reviewmentioning
confidence: 99%
“…(2020) have presented a review on business model design in the context of CE by descriptive/content analysis and show business model issues in a transition of CE. A bibliometric and science mapping analysis technique has been adpoted to develop a comprehensive view of sustainable luxury research (Shashi et al. , 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Centobelli et al (2020) have presented a review on business model design in the context of CE by descriptive/content analysis and show business model issues in a transition of CE. A bibliometric and science mapping analysis technique has been adpoted to develop a comprehensive view of sustainable luxury research (Shashi et al, 2021). Alhawari et al (2021) gave the crux of CE definitions in planning processes, eco-systems and supply chain by using 91 papers that also investigated the use of digital transformation and industry 4.0 to implement the CE.…”
Section: Introductionmentioning
confidence: 99%